A New Genre of Digital Texts That Explore Children’s Frame of Mind, Health Literacy Skills, and Behavioral Intentions for Obesity Prevention - Valerie A. Ubbes (Children, 2025)
Background: This project focuses on the relevance of using a health literacy approach to educating children about obesity prevention. The Habits of Health and Habits of Mind© model was used to write Electronic Texts for Health Literacy© to encourage actions that support obesity prevention. Guided by the Integrative Theory of Behavioral Prediction, the design template for a new genre of digital texts called Electronic Texts for Health Literacy© emerges for exploring children’s frame of mind, health literacy skills, and behavioral intentions toward obesity prevention. Methods: Online materials from selected websites were strategically reviewed for improving obesity prevention and child health literacy. The digital resources were juxtaposed with the Electronic Texts for Health Literacy©, with the latter written by and for children. Discussion: Health educators who use a constructivist pedagogy can help students to write health literacy narratives about obesity prevention, then read and talk about their multimodal compositions to further the practice and development of their health literacy skills. Children with obesogenic body frames can also gain from cowriting visual–textual–gestural health narratives with their peers or health professionals. Co-constructed narratives can help children make deeper connections about their identity, frame of mind, and social agency. Summary: Although this untested resource is available as a new genre of digital text, health educators could nudge children toward developing a stronger frame of mind and behavioral intentions toward obesity prevention when they write health literacy narratives that focus on decision making, goal setting, and communication in the context of eating nutritious foods and participating in physical activities.